Determinants of private commercial banks deposit in Ethiopia - Meseret Dame Tafa; Solomon Tessema Worku (Cogent Economics & Finance, 2022)
This study aimed to investigate the determinant of private commercial bank deposits in Ethiopia over eighteen years (2000-2017). To achieve the research objectives, an explanatory research design and a quantitative research approach were employed. In addition, the study has targeted sixteen private commercial banks currently operating in Ethiopia. Data obtained from selected banks were analyzed by using descriptive statistics and random effect model analysis. The regression result shows that three internal variables such as loan to deposit ratio, profitability and the number of bank branches and two macroeconomic variables such as unemployment rate and economic growth rate have a significant effect on the total deposit of private commercial banks. Based on the study finding, researchers recommended that all private commercial banks are required to aggressively expand their branches comparatively to the commercial bank of Ethiopia, and government bodies should give more attention to sustainable economic growth and should work on unemployment reduction.
Keywords: 330; Deposit mobilization; private commercial banks; remittance; deposit ratio; Ethiopia